Pengaruh Gaya Kepemimpinan Transformasional, Remunerasi Dan Disiplin Kerja Terhadap Kinerja Anggota Pangkalan TNI AL Tegal - Wahyudi, Catur; Jalil, Mahben (Jurnal Administrasi Karya Dharma, 2023)
The objectives of this research are  for knowing the effect of transformational leadership style, remuneration, and work discipline on the performance of members of the Tegal Navy Base. As wel as for knowing the effect of transformational leadership style, remuneration and work discipline together on the performance of members of the Tegal Navy Base. The research method used in this research is descriptive quantitative. Data collection techniques using the questionnaire method. While the data analysis technique used is the successive interval test method, classical assumption testing, multiple regression analysis, partial test, simultaneous test, and the coefficient of determination. The conclusions of this study are 1) partial testing of transformational leadership on the performance of members by using the t test obtained a value of sig = 0.000 <0.05 so it can be concluded that there is a significant effect of transformational leadership style on the performance of members of the Tegal Navy Base. 2) partial testing remuneration on the performance of members by using the t test obtained a value of sig = 0.000 <0.05 so it can be concluded that there is a significant effect of remuneration on the performance of members of the Tega Navy Base. 3) partial testing of work discipline on employee performance by using the t-test obtained a value of sig = 0.000 <0.05 so it can be concluded that there is a significant effect of work discipline on the performance of members of the Tegal Navy Base. 4). From the simultaneous test using SPSS, the value of sig = 0.000 <0.05, so it can be concluded that the model in this study is fit, or there is a significant effect of transformational leadership style, remuneration and work discipline together on the performance of members of the Indonesian Navy Base. Tegal.